FAKTOR FAKTOR RISIKO GANGGUAN FUNGSI KOGNITIF PADA PENYANDANG LUPUS ERITEMATOSUS SISTEMIK LES - Rakhmad Hidayat*, Diatri Nari Lastri**, Nanang Sukmana***, Herqutanto**** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION SYSTEMIC LUPUS ERYTHEMATOSUS SLE IS AN AUTOIMMUNE INFLAMMATORY CHRONIC DISEASE THAT COULD AFFECT THE NERVOUS SYSTEM WITH COGNITIVE IMPAIRMENT AS THE MOST FREQUENT MANIFESTATION THIS COGNITIVE IMPAIRMENT COULD INFLUENCE MORBIDITY AND MORTALITY OF SLE PATIENTS THE AIM OF THIS STUDY WAS TO IDENTIFY RISK FACTORS FOR THE PRESENCE OF COGNITIVE IMPAIRMENT IN SLE PATIENTS